Democratic Leadership Style and Constructive Feedback as Drivers of Generation Z Students' Academic Achievement - Monica Indi Gunawan Setia; Emiliana Sri Pudjiati; Nurchayati Nurchayati; Sukardi Sukardi (International Journal of Economics and Management Research, 2026)
The academic achievement of Generation Z students faces new challenges as higher education dynamics are increasingly shaped by instructional interaction styles and feedback quality. Theoretically, this study is grounded in democratic leadership theory (Avolio et al., 1999) and effective feedback theory (Kluger & DeNisi, 1996; Wisniewski et al., 2020). Research gap shows inconsistent findings regarding the simultaneous relationship of democratic leadership style and constructive feedback with academic achievement among Gen Z students in Indonesian higher education. Therefore, this study aims to analyze the relationship between democratic leadership style (X1) and constructive feedback (X2) on the academic achievement (Y) of Gen Z students at Universitas 17 Agustus 1945 Semarang. The study employs a quantitative correlational approach using Pearson Product Moment on 100 students selected through stratified proportional sampling. The results of the correlation test show that democratic leadership style has a positive and significant correlation with academic achievement (r = 0.699; sig. = 0.000), constructive feedback has a positive and significant correlation with academic achievement (r = 0.813; sig. = 0.000), and constructive feedback demonstrates a stronger correlation than democratic leadership style. These findings indicate that feedback quality is the dominant factor in promoting student academic achievement. The research recommends prioritizing faculty competency development in effective feedback delivery as the primary strategy for improving student academic achievement in higher education institutions.